Pre-school children's play behaviour influenced by classroom's spatial definitions? / Mohamed Yusoff Abbas, Mansor Othman and Puteri Zabariah Megat Abdul Rahman - Abbas, Mohamed Yusoff; Othman, Mansor; Megat Abdul Rahman, Puteri Zabariah (Universiti Teknologi MARA Cawangan Selangor, 2016)
Quality education is one of Malaysia's six KRAs (Key Result Areas) which has been accorded priority in the 2010 Budget, and in the planning of the 10'" Malaysia Plan 2011-2015. 0/ interest is the RMlOO million allocations under the 2010 budget to the Permata Negara programme which focuses on early childcare education. Despite this huge allocation, there currently appears to be a lot of emphasis on just the non-physical aspects of preschools. In more developed countries, the qualities of both the physical and non-physical aspects of preschool classrooms are given equal emphasis in providing quality education. Earlier research has established that the physical environment impacts children's behaviour and their progressive developments. Has the physical environment 0/ Malaysian preschools attained a standard of quality on par with developed nations? Based on an ongoing research project which investigated the relationship between the physical environment of public pre-schools and children's play behaviour, this paper focused on the influence of the spatial definitions of the classrooms upon the children's play behaviour. Three types of spatial definitions in existing pre-school classrooms and the children's five types of play behaviours were investigated. The research design strategised on surveys, while the methodology involved a pilot study, the use of questionnaire surveys, natural unobtrusive observations with video recordings, structured interviews and Moore's (2008) Children's Physical Environment Rating Scale (CPERS). Overall, the data collected involved observations upon 494 children in 20 classroom settings from the 10 public pre-schools located at both urban and non-urban locations within the Klang Valley in Malaysia. Data were analysed using the SPSS statistical analysis. The findings revealed that spatial definition of the classrooms had a significant effect on the children's behaviours. Implications in the design of future pre-school classrooms were discussed.